A major trade-off between growth and defense in Arabidopsis thaliana can vanish in field conditions. - Derek S Lundberg; Sonja Kersten; Ezgi Mehmetoğlu Boz; Pratchaya Pramoj Na Ayutthaya; Wangsheng Zhu; Karin Poersch; Wei Yuan; Sophia Swartz; David Müller; Ilja Bezrukov; HARVEST TEAM; Detlef Weigel (PLoS Biology)
When wild plants defend themselves from pathogens, this often comes with a trade-off: the same genes that protect a plant from disease can also reduce its growth and fecundity in the absence of pathogens. One protein implicated in a major growth-defense trade-off is ACCELERATED CELL DEATH 6 (ACD6), an ion channel that modulates salicylic acid (SA) synthesis to potentiate a wide range of defenses. Wild Arabidopsis thaliana populations maintain significant functional variation at the ACD6 locus, with some alleles making the protein hyperactive. In the greenhouse, plants with hyperactive ACD6 alleles are resistant to diverse pathogens, yet they are of smaller stature, their leaves senesce earlier, and they set fewer seeds compared to plants with the standard allele. We hypothesized that ACD6 hyperactivity would not only affect the growth of microbial pathogens but also more generally change leaf microbiome assembly. To test this in an ecologically meaningful context, we compared plants with hyperactive, standard, and defective ACD6 alleles in the same field-collected soil, both outdoors and in naturally lit and climate-controlled indoor conditions, taking advantage of near-isogenic lines as well as a natural accession and a CRISPR-edited derivative. We surveyed visual phenotypes, gene expression, hormone levels, seed production, and the microbiome in each environment. The genetic precision of CRISPR-edited plants allowed us to conclude that ACD6 genotype had no effect on mature field plants in our setting, despite reproducibly dramatic effects on greenhouse plants. We conclude that additional abiotic and/or microbial signals present outdoors-but not in the greenhouse-greatly modulate ACD6 activity. This raises the possibility that the fitness costs of other commonly studied immune system genes may be grossly misjudged without field studies.